A Macrofinance View of U.S. Sovereign CDS Premiums - CHERNOV, MIKHAIL; SCHMID, LUKAS; SCHNEIDER, ANDRES (Journal of Finance, 2020)
ABSTRACT Premiums on U.S. sovereign credit default swaps (CDS) have risen to persistently elevated levels since the financial crisis. We examine whether these premiums reflect the probability of a fiscal default—a state in which a balanced budget can no longer be restored by raising taxes or eroding the real value of debt by increasing inflation. We develop an equilibrium macrofinance model in which the fiscal and monetary policy stances jointly endogenously determine nominal debt, taxes, inflation, and growth. We show that the CDS premiums reflect the endogenous risk‐adjusted probabilities of fiscal default. The calibrated model is consistent with elevated levels of CDS premiums but leaves dynamic implications quantitatively unresolved.